2022
DOI: 10.1097/tp.0000000000004194
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Estrogen Receptor Modulator, Raloxifene, Is Protective Against Renal Ischemia–reperfusion Injury

Abstract: Background. There is increasing evidence that estrogen is responsible for improved outcomes in female kidney transplant recipients. Although the exact mechanism is not yet known, estrogen appears to exert its protective effects by ameliorating ischemia–reperfusion injury (IRI). In this study, we have examined whether the beneficial effects of exogenous estrogen in renal IRI are replicated by therapy with any one of several selective estrogen receptor modulators. Methods. C57BL/6 adult mice underwent standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…One study showed significantly less renal interstitial fibrosis in the RAL-treated group than in controls. In another study, RAL reduced renal tubular damage in a mice model with hereditary glomerulonephritis [38]. This renoprotective effect in rats can be explained by the ability of RAL to alter the balance of antioxidants by reducing levels of oxidative stress and increasing redox system activity.…”
Section: Histopathological Examinationmentioning
confidence: 92%
“…One study showed significantly less renal interstitial fibrosis in the RAL-treated group than in controls. In another study, RAL reduced renal tubular damage in a mice model with hereditary glomerulonephritis [38]. This renoprotective effect in rats can be explained by the ability of RAL to alter the balance of antioxidants by reducing levels of oxidative stress and increasing redox system activity.…”
Section: Histopathological Examinationmentioning
confidence: 92%
“…In young females, estrogens play a predominantly protective role, ameliorating the consequences of IRI while the protective effects of estrogens may be less pronounced with aging (54,66). In support, pre-clinical studies investigating the effects of selective estrogen receptor modulators and treatment suggest that the loss of protection in aging could at least in part be preserved (55,67).…”
Section: Aging and Biological Sex Affecting Ischemia Reperfusion Inju...mentioning
confidence: 95%